PENGARUH MODERASI SIZE TERHADAP HUBUNGAN ANTARA FAMILY CONTROL DENGAN NILAI DAN KINERJA PERUSAHAAN - Edi Supriyanto (Jurnal Ekonomi dan Bisnis, 2015)
This study investigates how family control affects the corporate values and performances.Then, We also test the effect of size moderation on relation between family control affects the corporate values and performances. The respondents are all of the corporates that listed in Jakarta Stock Exchanges (JSX) on 2004 until 2007. Purposive sampling is used to choosed data’s or samples. This study only gets 30 corporates of services from of them. Regresy Linier is used to analyzed this data’s, but before it we done classics assumption test. The result shows that variable of family control directly has not positive effect to the corporate values and performances. It is evidenced by statistic analysis with t-value -0,044 and level of significance about 0,816 for the first hypothesis and with t-value 0,156 and level of significance about 0,412 for the second hypothesis. It is not support prior research by Barontini dan Caprio (2005). The test of size moderation gets result that the corporate values and performances are effected by size of corporates. It’s evidenced by level of significance about 0.00.Keywords : Agency Theory, Family Control, Firm Value, Firm Performance.